2011
DOI: 10.1007/s10157-011-0423-3
|View full text |Cite
|
Sign up to set email alerts
|

A case of a 6-year-old girl with anti-neutrophil cytoplasmic autoantibody-negative pauci-immune crescentic glomerulonephritis

Abstract: A 6-year-old girl was admitted to our hospital with proteinuria, hematuria, skin rash and joint pain of the lower limbs. Due to rapid progression of renal insufficiency, hemodialysis and peritoneal dialysis were performed. She was diagnosed with rapidly progressive glomerulonephritis. Kidney biopsy showed severe crescent formation (50% of glomeruli) and no deposition of any immunoglobulins or complements. Serologically, anti-neutrophil cytoplasmic autoantibody (ANCA) was negative not only by ELISA against prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…Shimizu et al [5] observed neutrophil infiltration in the glomerular lesion and elevated IL-6 and IL-8 levels in the acute phase of ANCA-negative CrGN. Moreover, there have been a few reports of Th17 cells and IL-17 in patients with ANCAnegative CrGN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shimizu et al [5] observed neutrophil infiltration in the glomerular lesion and elevated IL-6 and IL-8 levels in the acute phase of ANCA-negative CrGN. Moreover, there have been a few reports of Th17 cells and IL-17 in patients with ANCAnegative CrGN.…”
Section: Discussionmentioning
confidence: 99%
“…ANCA also plays a crucial role in the initiation and progression of ANCA-associated CrGN, but a significant number patients with pauci-immune CrGN are negative for ANCA. ANCA-negative pauci-immune CrGN has been demonstrated in only a limited number of case reports [3][4][5][6]. The prevalence of this disease is approximately 10-30 % [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shimizu et al [8] observed neutrophil infiltration in the glomerular lesion and elevated IL-6 and IL-8 levels in the acute phase of ANCA-negative CrGN. Morikawa et al [5] reported a large amount of neutrophil infiltration in the glomerulus, with crescent formation, and significant elevated levels of IL-6, TGF-β, and IL-8 in the blood in their report of ANCA-negative pauci-immune CrGN patients associated with adenosquamous cell carcinoma of the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Отмечено, что острая фаза сопровождается нейтро-фильной инфильтрацией в клубочках [15,53], повышени-ем концентрации интерлейкинов 6 и 8 в крови [53]. Проду-кты дегрануляции нейтрофилов обнаруживают в сыворот-ке крови у АНЦА-негативных пациентов с рauci-иммун-ным ГН даже в более высокой концентрации, чем в АНЦА-позитивных случаях [21].…”
Section: таблицаunclassified